Clinical feasibility of high‐power short‐duration strategy at the sites adjacent to the esophagus during laser balloon‐based pulmonary vein isolation - Haruta Kato; Yoshihisa Naruse; Yutaro Kaneko; Taro Narumi; Makoto Sano; Yuichiro Maekawa (Journal of Arrhythmia)
Abstract Background Laser balloon‐based pulmonary vein isolation is an established therapeutic option for atrial fibrillation. However, elevated esophageal temperature is sometimes problematic and increases the risk of collateral esophageal damage. This study aimed to evaluate the efficacy and safety of different power settings at sites where sudden esophageal temperature increases were documented. Methods We enrolled 50 ablation sites in 11 patients where the esophageal temperature reached 39°C within 5 s after ablation. We applied four power settings (12, 10, 8.5, and 5.5 W), and ablation was immediately stopped when the esophageal temperature reached 39°C. Efficacy outcomes included ablation time and total energy, calculated as the product of power and ablation time. Safety outcomes included maximal esophageal temperature and area under the temperature–time curve above 39°C. Results Although ablation time was the longest in the 5.5 W group (12 W: 3.1 ± 2.1 s, 10 W: 3.6 ± 2.7 s, 8.5 W: 4.7 ± 3.9 s, 5.5 W: 8.0 ± 7.2 s; p < 0.001), total energy did not differ among the four groups (40 ± 35, 35 ± 26, 38 ± 31, and 40 ± 39 J, respectively; p = 0.864). There were no significant differences in maximal esophageal temperature (40.2 ± 1.7, 40.3 ± 1.9, 40.1 ± 1.5, and 39.8 ± 1.1°C, respectively; p = 0.532) or the area under the temperature–time curve above 39°C (16 ± 49, 18 ± 57, 12 ± 29, and 7 ± 14°C･t, respectively; p = 0.564) among the four groups. Conclusions A high‐power, short‐duration strategy might allow comparable energy application without excessive esophageal collateral damage, as estimated by the esophageal temperature. However, further research using gastrointestinal endoscopy to evaluate esophageal injury is needed to confirm our results.